Brexit, Trumpism and paradox: epistemological lessons for the critical consensus - Vine, Tom. (Organization)
Brexit and the election of Donald Trump can be interpreted as the culmination of a chain of events beginning with neoliberalism. This certainly appears to be the position we critical scholars have adopted. We readily paint neoliberalism as our ideological nemesis and cite it as the reason the developed world faced austerity measures in the late 2000s and early 2010s. And it is austerity, we tell ourselves, that led to the electoral surprises of 2016. In this article, I invoke the epistemological nuance found in Kierkegaard, Nietzsche and Weber to re-evaluate this linear cause-and-effect logic. Linear thinking is borne of a broader epistemological bias, a bias which the world of physics, for example, has long abandoned. However, linear thinking continues to pervade critical management studies, especially where it yields results consistent with our leftist inclinations. As critical management theorists, our ontological predisposition to continually rationalise macrosociological shifts in respect of oversimplified linear thinking reveals crude ideological conviction, political prejudice and identity anxiety. This article suggests that we can usefully reflect on the events of 2016 such that critical management studies can (1) dislodge itself from its ideological biases; (2) move away from overly simplistic cause-and-effect thinking and instead pay greater attention to nonlinear logic including, in particular, the pedagogical potential of paradox; (3) actively engage across disciplinary boundaries; and (4) breathe new life into truly ethnographic endeavours to better understand the sorts of factors that contributed to Brexit and Trump$1 (Bs election in the first place.- Reproduced s
Keywords: Brexit, Critical management studies, Critical theory, Epistemology, Ethnography, Ethnomasochism, Nonlinear logic, Paradox, Polemic, Trump